Antihyperlipidemic Activity of Trembesi Leaf Extract (Samanea saman) Against Total and LDL Cholesterol Levels in Hypercholesterolemic Mice - Rosa Juwita Hesturini (Sean Institute, 2023)
The potential of the trembesi plant (Samanea saman) which is used for traditional medicine includes antibacterial, analgesic, treating headaches and diarrhea [1]. Trembesi leaves are known to have several chemical compounds such as flavonoids, alkaloids, tannins, saponins, and steroids or triterpenoids which are thought to have activity in reducing total cholesterol levels [2]. The aim of this study was to determine the activity and optimal dose of trembesi leaf extract which can reduce total and LDL cholesterol levels in hypercholesterolemic mice. Research method: 25 test mice were divided into 5 groups consisting of group 1 given CMC-NA 1% negative control, group 2 given simvastatin 10 mg positive control, groups 3, 4 and 5 were given extract treatment trembesi leaves with doses of 35 mg/KgBW, 175 mg/KgBW and 350 mg/KgBW. The mice tested were given atherogenic feed and then examined for total and LDL cholesterol levels using the CHOD PAP enzymatic method. Data analysis used the one-way ANOVA test, followed by the post hoc test, namely Duncan's test. Results: Ethanol extract of trembesi leaves at a dose of 175 mg/KgBW can reduce total cholesterol levels by 37.07% and LDL by 50.24%. Conclusion: ethanol extract of trembesi leaves at a dose of 175 mg/KgBW provides an optimal effect on reducing total and LDL cholesterol levels (p<0.05).